Refugees from Africa: Can a Marshall Plan help? - Stefan Mair (Stiftung Wissenschaft und Politik (SWP), 2004)
The recent relief action carried out by the organization Cap Anamur in the Mediterranean Sea has met considerable response in the German media. It did not only result in a debate on the treatment of refugees from Africa and on the EU asylum policy but also on the situation of the refugees' region of origin. The point of departure in many media reports is to ask whether it would be better to undertake measures at the source of refugee stream, rather than to get tangled up in the issue of how the stream can be held back at Europe's gates. In other words, wouldn't it be better to combat the causes for seeking refuge rather than act against the refugees? Though it is easy to achieve consensus across the political spectrum for the idea of attacking the problem at its roots, the majority of proposals published to date do not do justice to the complexity of the matter. (SWP Comments / SWP)
Keywords: 320